Eficiência da aplicação superficial de calcário em áreas de café em produção - Faria, Mauro Magalhães Leite (2021)
Coffee is one of the main crops in Brazilian agribusiness, with Brazil being the world's largest producer and exporter of the bean. Many soils where coffee crops are planted have high acidity, high levels of Al3+ and low availability of nutrients, making liming indispensable for cultivation. The objective was to evaluate the efficiency of surface liming in the correction of soil acidity, plant nutrition and productivity and the quality of Arabica coffee drink. To this end, two field experiments were installed in the mesoregion of the “slope fields” in the state of Minas Gerais - Brazil, under a clayey Red-Yellow Latosol. At each site, a randomized block design (DBC) was used, with five limestone doses (0, 3, 6, 12 and 24 tons per hectare), applied on the surface and four replications. The influence of the limestone doses on the chemical attributes of the soil in the layers 0.0 to 0.1, 0.1 to 0.2 and 0.2 to 0.4 m was evaluated, as well as the concentrations of nutrients in the leaves, in the first and second year after application. The productivity, granulometry and quality of the drink were also evaluated in the 2020 harvest. The lime applied superficially did not cause significant effects on the chemical attributes of the soils in the analyzed layers, nor on the levels of macro and micronutrients in the leaves, without altering the productivity, quality physical and sensory effects of the grains produced.